MULTICRITERIA DECISION AID TO IMPLEMENT AN ON-FARM STORAGE SYSTEM FOR SOYBEANS - Bocca,Lucas S. (2016)
ABSTRACT: Implementing an on-farm storage system for agricultural products becomes a complex decision problem when considering risks, benefits, uncertainties and alternatives. This study aimed at applying the multicriteria decision aid (MCDA) approach to select the infrastructure to be implemented, taking into account variables and farmer's goals. As a result, we concluded that the adopted approach was useful since it allowed a better understanding of the problem and provided decision-making support.